2007
DOI: 10.1080/01904160701615442
|View full text |Cite
|
Sign up to set email alerts
|

Dry Weight and Nitrogen Content of Chickpea and Winter Wheat Grown in Pots for Three Rotations

Abstract: Chickpea [Cicer arietinum (L.)] cultivars 'ICCV-2' and 'Sarah' were studied along with a control, multistrain, TAL 1148, and TAL 480 Bradyrhizobium strains to determine the effect(s) of cultivar and inoculum on dry weight (DW) and nitrogen (N) content of the legume, as well as soil mineral N, DW, and N content of wheat [Triticum aestivum (L.) emend. Thell.] in a continuous wheat-legume rotation. Chickpeas were planted during the summer and harvested in the fall of 1992, 1993, and 1994. Vegetative growth from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…Additionally, the flux rates from cowpea treatments were significantly lower than from the 45-N and 90-N treatments. These results corroborate the previous findings in the region, as poor growth and yield responses of winter wheat to legume-based green N are reported frequently [3,4,25,27,28]. Lack of interaction effects between the tillage systems and N treatments indicated that cowpea-based green manure could not replace inorganic N fertilizers in either tillage system.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, the flux rates from cowpea treatments were significantly lower than from the 45-N and 90-N treatments. These results corroborate the previous findings in the region, as poor growth and yield responses of winter wheat to legume-based green N are reported frequently [3,4,25,27,28]. Lack of interaction effects between the tillage systems and N treatments indicated that cowpea-based green manure could not replace inorganic N fertilizers in either tillage system.…”
Section: Discussionsupporting
confidence: 90%
“…Canopy fluxes of CO 2 increased with increasing rates of N fertilizer, which indicated strong growth responses of winter wheat to amounts of applied N fertilizer. Increased GPP fluxes with increasing level of N fertilizer corroborate results from previous studies in the SGP, where most studies reported strong positive responses of grain or forage yield of winter wheat to amount of applied N fertilizer [4,24,25]. The results of canopy CO 2 fluxes also corroborate results on crop growth and yield of winter wheat, which was reported in a parallel study [26].…”
Section: Discussionsupporting
confidence: 87%